Antecedents of Strategic Planning of SMEs in Malaysia: The Influence of Ownership Motivations and Environmental Uncertainty - Marn, Joel Tham Kah; Hin, Cheng Wei; Bohari, Abdul Manaf (International Review of Management and Marketing, 2016)
The main purpose of this study is to empirically determine the major forces influencing the degree of strategic planning adopted by small and medium enterprises in Malaysia. In particular, the study critically examines the influences that ownership motivation and environmental uncertainty could be significant antecedents in determining strategic planning practice among the SME sector. After the extend literatures, this study developed a positivist paradigm using quantitative methods. Data were collected from the portal set up by Small and Medium Industries Development Corporation (SMIDEC) which in turn is the secretariat to the National SME Development Council (NSDC) using multiple regressions to analyses. Both ownership motivation and environmental uncertainty are found to influence significantly the level of strategic planning exhibited within the SMEs surveyed. The policy maker and academics can make use of this study as a contribution to literature. Necessary recommendation and recommendation for future studies were discussed. Keywords: Ownership motivation, Environmental Uncertainty, Strategic Planning Process JEL Classifications: L0, M1